English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

5 answers

6 DUH!!!!

2007-01-27 04:42:13 · answer #1 · answered by A leap in the right direction. 2 · 0 0

(x + 1)(2x - 3)(3x - 4) = Ax^3 + Bx^2 + Cx + D
(2x^2 - x -3)(3x - 4) = Ax^3 + Bx^2 + Cx + D
6x^3 - 8x^2 - 3x^2 +4x -9x + 12 = Ax^3 + Bx^2 + Cx + D
6x^3 - 11x^2 - 5x + 12 = Ax^3 + Bx^2 + Cx + D
only if
A = 6
B = -11
C = -5
D = 12

many thanks
God "Allah" help us.

2007-01-27 12:51:12 · answer #2 · answered by shamshona 2 · 0 0

Ax^3 = 6x^3
so A=6

2007-01-27 12:45:08 · answer #3 · answered by Geinius 3 · 0 0

Ax^3 = x*2x*3x = 6x^3
A=6

2007-01-27 12:39:52 · answer #4 · answered by J 2 · 0 0

6.

2007-01-27 12:44:03 · answer #5 · answered by David 3 · 0 0

fedest.com, questions and answers